Surviving Your Thesis, 1st edition - Suzan, Burton (Routledge, 2020)
From choosing a supervisor and topic to staying motivated, completing a research thesis is not an easy matter. Each stage represents a different challenge and many students struggle through without identifying the skills needed to make the most of their time.